2022
DOI: 10.31083/j.fbl2701005
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 limits the cytotoxic activity of TAK-243, an inhibitor of the ubiquitin-activating enzyme UBA1

Abstract: Background: One of the major concerns of cancer therapy is the emergence of multidrug resistance (MDR). The MDR-associated ATPbinding cassette sub-family B member 1 (ABCB1) transporter is established to mediate resistance against numerous anticancer drugs. In this study, we demonstrated that the Ubiquitin-like modifier activating enzyme 1 (UBA1) inhibitor TAK-243 is transported by the ABCB1. Methods: MTT assay was performed to evaluate the cytotoxicity of TAK-243. Western blot was carried out to investigate if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Because TAK-243 has been reported to be a substrate for the drug efflux P-glycoprotein pumps ( 29 ), we tested the expression of the ATP-binding cassette transporters MDR-1 ( ABCB1 ) and BCRP ( ABCG2 ). Consistent with the report that genetically engineered ABCB1-overexpressing colon SW620, kidney HEK, and mouth epithelial KB cells are highly resistant to TAK-243, we found that the NCI-H295R and CU-ACC1 cell line overexpress MDR1 and are the most resistant to TAK-243 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because TAK-243 has been reported to be a substrate for the drug efflux P-glycoprotein pumps ( 29 ), we tested the expression of the ATP-binding cassette transporters MDR-1 ( ABCB1 ) and BCRP ( ABCG2 ). Consistent with the report that genetically engineered ABCB1-overexpressing colon SW620, kidney HEK, and mouth epithelial KB cells are highly resistant to TAK-243, we found that the NCI-H295R and CU-ACC1 cell line overexpress MDR1 and are the most resistant to TAK-243 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of MDR1 and SLFN11 are potential predictors of TAK-243 response. Increased expression of the ABC transporter MDR1 has been associated with decreased TAK-243 sensitivity ( 29 ). Accordingly, we found that the ACC cell lines, NCI-H295R and CU-ACC1, which express ABCB1 , the gene encoding MDR1/PgP, are less sensitive to TAK-243 than the CU-ACC2 cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Till now, many ABC members were found to be overexpressed in the cancer cells, responsible for transporting certain anti-tumor drug(s) out from the cells, voiding overaccumulation of intracellular drug or blockage of the pathways necessary for cell survival 13 , 14 . The two most famous ABCB1/P-glycoprotein (P-gp) and ABCG2/Breast cancer resistance protein (BCRP) transporters, which were confirmed to have transmembrane domain(s) [TMD(s)] and cytoplasmic nucleotide-binding domain(s) [NBD(s)] 15 , 16 , 17 , exhibited strong ability to keep pumping various substrate anti-tumor drugs (including inhibitors) out, such as KRAS-G12C inhibitor ARS-1620, Aurora kinase inhibitor GSK1070916, paclitaxel, doxorubicin, and TAK-243, an inhibitor of the ubiquitin-activating enzyme UBA1 for ABCB1 and mitoxantrone, ubiquitin activating enzyme (UAE) inhibitor MLN7243 for ABCG2 4 , 11 , 18 , 19 , 20 , 21 , 22 . ABCC1/MRP1, which mediates MDR in several types of cancer, including lung, childhood neuroblastoma, ovary, prostate, and breast cancers, can transport a variety of substrates including drugs, toxic molecules and important physiological substrates like lipid peroxidation products, for example, S -(6-(7- 11 C-methylpurinyl))glutathione [ 11 C-MPG], lipid peroxidation products, GSSG, and reduced glutathione (GSH) 23 , 24 , 25 , 26 .…”
Section: Drug Resistance-related Factors and Signalsmentioning
confidence: 99%
“…The binding could compete with unlabeled taxol. [ 3 H]­Taxol continues to be employed in studies of taxane-site ligand interactions …”
Section: Photaffinity Labeling Of Tubulinmentioning
confidence: 99%